ANALISIS KUALITAS SOAL THREE TIER TEST MENGGUNAKAN TEORI RESPON BUTIR KLASIK : QUALITY ANALYSIS OF THREE TIER TEST QUESTIONS FINAL SEMESTER EXAMS OF BASIC PHYSICS COURSES USING CLASSICAL ITEM RESPONSE THEORY - Anas Irwan; Ahmat Purwadi Saleh Kerans (Pendidikan Fisika UIN Alauddin Makassar, 2022)
The research was conducted with the aim of determining the quality of the three-tier test questions for the final semester exam for basic physics 1 course using classical item response theory in students of the Physics Education Study Program, Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. This type of research is a mix methode with a multiphase design research design. This research was conducted at the Physics Education Study Program, Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. The results showed that the content validity test conducted with the Gregory test showed a validity level of 0.9 and the construct validity test obtained 28 valid items and 12 invalid items, while the reliability test using Alpha Cronbach obtained 0.6045 (quite reliable). From the results of the analysis of the quality of the questions obtained as many as 11 good grains, as many as 20 grains are enough and as many as 9 grains are not good. The impilation of this lamp is a question that has good quality and is good enough to be used as a question bank, while the question item that is not good should be revised